PENGARUH METODE PEMBELAJARAN DAN KOORDINASI GERAK TERHADAP HASIL BELAJAR PERMAINAN BOLA BASKET (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
AbstrakPenelitian ini bertujuan untuk mengetahui : 1) Perbedaan metode pembelajaran langsung / directinstruction dan tugas terhadap hasil belajar permainan bolabasket. 2) Perbedaan antara koordinasigerak tinggi dan rendah terhadap hasil belajar permainan bolabasket. 3) Interaksi antara metodepembelajaran dan koordinasi gerak terhadap hasil belajar permainan bolabasket. Penelitian inimenggunakan metode eksperimen dengan rancangan faktorial 2 x 2. Populasi penelitian adalahsiswa kelas VIII SMP Negeri 17 Semarang berjumlah 238 siswa. Teknik sampling yang digunakanadalah purposive random sampling, sampel yang diambil sebanyak 40 siswa terdiri dari 20 siswayang memiliki koordinasi gerak tinggi dan 20 siswa yang memiliki koordinasi gerak rendah. Hasilpenelitian diperoleh : 1) Perhitungan hasil belajar bolabasket F_(hit )21,127 > F_tab 4,113, perbandinganrata-rata nilai pembelajaran metode direct instruction 85,65 > 82,55 metode tugas. 2) Hasilperhitungan F_hit 35,557 > F_tab 4,113, dengan rata-rata nilai koordinasi gerak tinggi 86,0 > 82,20nilai koordinasi gerak rendah. 3) Terdapat interaksi antara metode pembelajaran dan koordinasigerak terhadap hasil belajar permainan bolabasket dengan hasil F_hit 4,161 > F_tab4,113. Kesimpulan: (1) Ada perbedaan pengaruh hasil pembelajaran antara metode pembelajaran langsung danmetode tugas terhadap hasil belajar permainan bolabasket. Hasil belajar bolabasket dengan metodepembelajaran langsung lebih baik dari pada metode tugas. (2) Ada perbedaan pengaruh antara koordinasigerak tinggi dan koordinasi gerak rendah terhadap hasil belajar permainan bolabasket. (3) Terdapatinteraksi antara metode pembelajaran dan koordinasi gerak terhadap hasil belajar permainanbolabasket. Saran yang dapat disampaikan adalah metode pembelajaran direct instruction dapatdigunakan sebagai alternatif metode pembelajaran bagi para guru penjasorkes dalam meningkatkanhasil belajar permainan bolabasket.AbstractThe purpose of this study is to determine : (1) The difference between direct instructional method and task method onresult of basketball study. (2) The difference between the high and low move coordination on the result of basketballstudy. (3) The interaction between learning methods and move coordination as the result of basketball study. This studyuses an experimental method with 2 x 2 factorial design. The population is VIII grade junior high school student of SMPN 17 Semarang, academic year 2011/2012, 238 students. Sampling technique used was purposive random sampling,by selecting 40 students, consist of 20 student who have a high move coordination and the 20 students who have a lowmove coordination. Variables studied were independent variables consisted of two factors namely the manipulativevariable and atributive variables, and one the dependent variable. Manipulative variable consists of direct instructionmethod, and task methods. Atributive variable consists of a group of move coordination of sample with high and low.Dependent variable in this study is the results of basketball. Data colection tehcniques use the test and measurenment.Retrieval of data basketball study result uses study basketball result test. Hand,eye, and food coordinations of dataretrieval is done by throwing, catching, and kicking the hand ball. Data analysis techniques in the sudy use analysis ofvariance and hypothesis testing by calculating the F test at a significance level of 5 % and Tukey-test. The result obtained:1) The result of basketball study to the students with direct instruction method F_(hit )21,127 > F_tab 4,113, and theresult of basketball study obtained an average of 85,65 > 82,55 from task method; 2) The basketball study result of thestudents with a high move coordination F_hit 35,557 > F_tab 4,113, obtained an average yield of 86,0 > 82,20from the students with low move coordination; 3) There is interaction between learning method and move coordinationas the result of basketball, the calculation is F_hit 4,161 > F_tab4,113. Conclusions: 1) There are differences in learningoutcomes between direct instructional method and task method as the result of basketball study; 2) There is a differenteffect between the high and low move coordination as the result of basketball study; 3) There is an interaction betweenlearning method and move coordination as the result of basketball study. Because the direct instruction method canincrease the result of basketball study, the physical education teacher is recommended to apply this to improve the resultof basketball study game.